Synchronization of gigahertz core resonances in multiple photonic crystal fiber cores by timing-modulated harmonic mode locking - Yeh, Dung-Han; He, Wenbin; Pang, Meng; Jiang, Xin; Russell, Philip St. J. (Optica, 2021)
Synchronization of mechanical oscillators by optical forces is a topic that has been much explored in recent years, for example, in the context of SiN microdisk resonators. Here we report stable long-termsynchronization of the core vibrations of three different photonic crystal fibers, driven intra-cavity by a 2 GHz train of timing-modulated pulses in a high harmonic opto-acoustically mode-locked fiber laser. The core resonances are equally spaced in frequency and are coupled purely by the optical field. Under the correct conditions, they become stably synchronized, being simultaneously driven by the timing-modulated pulse train. Floquet-Bloch theory, in which the pulses are treated as particles trapped in potential wells and coupled by optomechanical back-action, describes the complex temporal dynamics observed in the experiments. This unique system provides a novel means of modifying the temporal structure of pulse trains running at few-gigahertz repetition rates. (C) 2021 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2021-12-31